FEATURES OF THE MICROBIAL SPECTRUM UROGENITAL SYSTEM OF WOMEN WITH RECURRENT PYELONEPHRITIS - O. Romanenko; N. Stepanova; A. Rudenko; V. Kruglikov; L. Lebid; M. Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of our research was to identify the peculiarities of the microbial spectrum urogenital system of the women with recurrent pyelonephritis.Materials and methods. We have conducted a comprehensive micro-biological examination different biological material (urine, vaginal swabs, scraping of urethral and cervical canal’s) of 175 women with recurrent pyelonephritis. The patients were divided in accordance with frequency of recurrent. The microbial spectrum urogenital system of 98 women with recurrent pyelonephritis (group 1) was compared with 77 women with sporadic pyelonephritis (up to 2 times per year) (group 2). The research included the process of identification of bacterial agents, mollicutes, chlamydia as well as yeasts.Results. In the women with recurrent pyelonephritis had the significant increase of frequency of identification of E. faecalis in urine (p=0.03), in urethral canal (p=0.05), and vaginal scraping (p=0.02). 48 women from 1st group had bacterial mix-infection. At the same time, the women from comparative group had only in 25 (32.6%) cases (p=0.027). The direct associative relationship was found between existence of S. epidermidis in urethral canal, in cervical canal, in vagina and the frequency of recurrent pyelonephritis (ρ=0.2, р=0.009; ρ=0.23, р=0.004 and ρ=0.19, р=0.01 respectively); E. faecalis in the urethral canal (ρ=0.19, р=0.02); Candida albicans in the vagina (ρ=0.17, р=0.03). 79.6% examined patients were infected by mollicutes, viruses and chlamydia.Conclusions. Consistent high level of urethral’s and vaginal’s bacterial weight of the women with recurrent pyelonephritis leads to the migration of causative agents into bladder and to activates formation of recurrent of the disease. Identified peculiarities of microbial spectrum prove the necessity mandatory micro-biological research not only urine, but urethra, cervical canal, and vagina.